Social Media in Reference to Automobile Sector - Bhargava, Aparna; Kumar, Sudhir (Journal of Commerce and Trade, 2016)
Indian market is one of the largest markets of cars. The rising income levels of an individual especially middle class family has lift up their standards of living and has diverted their purchases towards commodities which can make their lives more comfortable. This has given a tremendous encouragement in the growth of automobile sector in India. With the growing vast popularity of the social media, from the manufacturers to the dealers, the entire automobile industry is embracing towards the social media for its promotions. This paper is an attempt to study the growing popularity of social media and its impact on the audience and hence the automobile sector must take advantage of this medium in order to gain publicity.